Cross-Talk between Adiponectin and IGF-IR in Breast Cancer - Mauro, Loredana; Naimo, Giuseppina Daniela; Ricchio, Emilia; Panno, Maria Luisa; Andò, Sebastiano (Frontiers in Oncology, 2015)
Obesity is a chronic and multifactorial disorder that is reaching epidemic proportions. It is characterized by an enlarged mass of adipose tissue caused by a combination of size increase of preexisting adipocytes (hypertrophy) and de novo adipocyte differentiation (hyperplasia). Obesity is related to many metabolic disorders like hypertension, type 2 diabetes, metabolic syndrome, and cardiovascular disease, and it is associated with an increased risk of cancer development in different tissues including breast. Adipose tissue is now regarded as not just a storage reservoir for excess energy, but rather as an endocrine organ, secreting a large number of bioactive molecules called adipokines. Among these, adiponectin represents the most abundant adipose tissue-excreted protein, which exhibits insulin sensitizing, anti-inflammatory, and antiatherogenic properties. The serum concentrations of adiponectin are inversely correlated with body mass index. Recently, low levels of plasma adiponectin have been associated with an increased risk for obesity-related cancers and development of more aggressive phenotype, concomitantly with alterations in the bioavailability of insulin-like growth factor-I (IGF-I) and IGF-I receptor (IGF-IR) signaling pathways. In this review, we discuss the cross-talk between adiponectin/AdipoR1 and IGF-I/IGF-IR in breast cancer.